Ḥadīth and Ethics through the Lens of Interdisciplinarity الحديث والأخلاق: مقاربة متعددة التخصصات - al-Khatib, Mutaz (Brill, 2022)
This volume addresses the interplay of ḥadīth and ethics and contributes to examining the emerging field of ḥadīth-based ethics. The chapters cover four different sections: noble virtues (makārim al-akhlāq) and virtuous acts (faḍāʾil al-aʿmāl); concepts (adab, taḥbīb, ʿuzla); disciplines (ḥadīth transmission, gender ethics); and individual and key traditions (the ḥadīth of intention, consult your heart, key ḥadīths). The volume concludes with a chronologically ordered annotated bibliography of the key primary sources in the Islamic tradition with relevance to understanding the interplay of ḥadīth and ethics. This volume will be beneficial to researchers in the fields of Islamic ethics, ḥadīth studies, moral philosophy, scriptural ethics, religious ethics, and narrative ethics, in addition to Islamic and religious studies in general. Contributors Faqihuddin Abdul Kodir, Nuha Alshaar, Safwan Amir, Khairil Husaini Bin Jamil, Pieter Coppens, Chafik Graiguer, M. Imran Khan, Mutaz al-Khatib, Salahudheen Kozhithodi and Ali Altaf Mian. يتناول هذا الكتاب الصلة بين الحديث والأخلاق، الأمر الذي لم يحظ بالاهتمام في الدراسات المعاصرة حول الأخلاق الإسلامية. فهو يؤسس لفرع أخلاقي جديد اسمه «الأخلاق الحديثية» التي تشكل مع أخلاق القرآن ما يسمى «الأخلاق النصية». يغطي الكتاب جوانب نظرية وأخرى تطبيقية. فهو يبرز المضمون الأخلاقي الثري لمدونات الحديث، ويضم أربعة أقسام رئيسة هي: مكارم الأخلاق وفضائل الأعمال، ومفاهيم: الأدب والتحبيب والعزلة، كما يتناول الأبعاد الأخلاقية لرواية الحديث والجندر (النوع الاجتماعي)، بالإضافة إلى الأحاديث المفردة (كحديث إنما الأعمال بالنيات، وحديث استفتِ قلبك) والأحاديث الكلية التي تشكل أصول الحديث ومبادئه الكبرى. يحتوي الكتاب أيضًا على كشاف تحليليّ لأبرز مصنفات المحدثين في الأخلاق. من شأن هذا الكتاب أن يكون مرجعًا للطلاب والباحثين في المجالات الآتية: الأخلاق الإسلامية، والحديث النبوي، والفلسفة الأخلاقية، والأخلاق النصية، والأخلاق الدينية، وأخلاقيات السرد، بالإضافة إلى الدراسات الإسلامية والدينية بشكل عام. المساهمون شفيق اكّريكّر، وصفوان أمير، وخَيرئيل حسيني بن جميل، ومحمد عمران خان، ومعتز الخطيب، ونهى الشعار، وفقيه الدين عبد القدير، وپيتر كوپنس، وصلاح الدين كوزيتودي، وعلي ألطاف ميان